2019
DOI: 10.4097/kja.d.18.00333
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of P values for demographic data in randomized controlled trials

Abstract: In a large number of randomized controlled trials, researchers provide P values for demographic data, which are commonly reported in table 1 of the article for the purpose of emphasizing the lack of differences between or among groups. As such, the authors intend to demonstrate that statistically insignificant P values in the demographic data confirm that group randomization was adequately performed. However, statistically insignificant P values do not necessarily reflect successful randomization. It is more i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Although participants will be randomly assigned (in groups of about 5-7 individuals) to either the TMI Adjunct or Standard Care Alone conditions, imbalance between the two groups on some of the baseline characteristics may occur. However, since assignment to treatment condition is random, any differences that arise are due to random chance [57,58]. We will present balance tables of baseline data to confirm the two groups are similar.…”
Section: Preliminary Analysesmentioning
confidence: 90%
“…Although participants will be randomly assigned (in groups of about 5-7 individuals) to either the TMI Adjunct or Standard Care Alone conditions, imbalance between the two groups on some of the baseline characteristics may occur. However, since assignment to treatment condition is random, any differences that arise are due to random chance [57,58]. We will present balance tables of baseline data to confirm the two groups are similar.…”
Section: Preliminary Analysesmentioning
confidence: 90%
“…Previous studies have examined the percentage of randomised trials that erroneously used p-values to compare randomised groups [1,44]. A study of over 300 trials from 2010 to 2017 in one journal and found 27% used p-values in tables [44].…”
Section: Relation Previous Workmentioning
confidence: 99%
“…Previous studies have examined the percentage of randomised trials that erroneously used p-values to compare randomised groups [1,44]. A study of over 300 trials from 2010 to 2017 in one journal and found 27% used p-values in tables [44]. An older study examined 50 trials from four high pro le journals and found that 48% included signi cance tests [1].…”
Section: Relation Previous Workmentioning
confidence: 99%
“…In this issue of the Korean Journal of Anesthesiology (KJA), Ahn et al [5] evaluated a total of 312 randomized controlled trials published in the Journal of Anesthesiology between 2010 and 2017 analyzing Table 1 presented in each study. The authors concluded that, unlike the intentions of the researchers, it was not important to present P values in Table 1 as a means of showing that the random assignment has been carried out properly.…”
mentioning
confidence: 99%